Enhancing sport brand preference in football: A psycho-branding model - Jaberi, Akbar; Zagalaz-Sánchez, María Luisa (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Objectives: Given the great significance of psychological concepts in explaining consumers’ behavior in sport settings, the aim of this study was to provide a sport psycho-branding model including self-definitional needs, brand equity, and brand preference. Methods: A field study was conducted at 521 FC Persepolis football fans in Iran to fulfil the research objectives. Data was collected by distributing a valid and reliable questionnaire at weekday home competition of FC Persepolis team. The research sample was selected through convenience sampling from the fans who attended the games of FC Persepolis from January to February 2022. Results: A Partial Least Squares Structural Equation Modeling revealed that: (a) self-definitional need principles were significantly related to the brand equity of FC Persepolis team, and (b) the brand equity was a significant predictor of fans’ brand preference. The findings highlight the significance of the fans’ psychological needs in improving the brand positioning of football teams. Conclusions: The proposed sport psycho-branding model includes self-definitional principles to facilitate the development of brand equity and the brand preference through an integrated model in football setting. This may be the first attempt to study these constructs through an integrated model in the branding process of a football team.